PEMBELAJARAN KETERAMPILAN MENULIS TEKS EKSPLANASI PADA SISWA SEKOLAH DASAR KELAS V DENGAN MENGGUNAKAN METODE INQUIRY LEARNING DENGAN SETTING MIND MAPPING TECHNIQUE - Desi Trisna Sari; Ruli Setiyadi (COLLASE (Creative of Learning Students Elementary Education), 2020)
ABSTRACT"Learning Text Writing Skills for Students in Class V by Using the Inquiry Learning Method with the setting Mind Mapping Technique ". Students still find it difficult to use the correct grammar and tenses, and they also lack ideas and are not interested in writing. The teacher also found it difficult to find explanation text teaching techniques to improve students' writing skills. This study aims to describe (1) the scenario and implementation of learning to write explanation texts for fifth grade students using the inquiry learning method with the setting mind mapping technique; (2) the fifth grade students' responses to learning to write explanation texts using the inquiry learning method with the setting mind mapping technique; (3) what difficulties experienced by the fifth grade elementary school students in completing explanation text writing assignments. This qualitative descriptive study consisted of four components, namely tests, observations, questionnaires, and documentation. The subjects of students in the VC grade at SDN I Cipeundeuy . In collecting data used test and non-test techniques. Based on the results of research on 30 students it is known that the average skill of students in writing explanatory texts is 76.63 out of a total score of 100 with a conversion value of 3.04 or predicate B. The results of research on students' explanatory text writing skills are based on aspects of content, organization, vocabulary, use of language, and mechanics is good. However, students still find it difficult to develop sentences from existing ideas. In addition, students still often make mistakes in writing the contents and structure of the text. The author wants to suggest the teacher to use the inquiry learning method with the setting mind mapping technique in teaching writing explanation texts, because the method can promote fun expressions in writing, so that it gets greater participation among students.  Kata Kunci: Explanation text , Inquiry Learning Method , Mind Mapping Technique.                                                                      ABSTRAK”Pembelajaran Keterampilan Menulis Teks Eksplanasi Pada Siswa Kelas V dengan Menggunakan Metode Inquiry Learning dengan setting Mind Mapping Technique”. Siswa masih menemukan kesulitan untuk menggunakan tata bahasa dan bentuk kata yang benar, dan mereka juga kekurangan ide dan tidak tertarik untuk menulis. Guru juga menemukan kesulitan untuk menemukan teknik mengajar teks eksplanasi untuk meningkatkan keterampilan menulis siswa. Penelitian ini bertujuan untuk mendeskripsi (1) skenario dan implementasi pembelajaran menulis teks eksplanasi siswa kelas v dengan menggunakan metode inquiry learning dengan setting mind mapping technique; (2) respon siswa kelas v terhadap pembelajaran menulis teks eksplanasi dengan menggunakan metode inquiry learning dengan setting mind mapping technique; (3) kesulitan – kesulitan apa yang dialami siswa SD kelas v dalam menyelesaikan tugas – tugas menulis teks eksplanasi. Penelitian desktiptif kualitatif ini terdiri dari empat komponen, yaitu tes, observasi, angket, dan dokumentasi. Subjek penelitian ini adalah siswa kelas VC SDN I Cipeundeuy. Dalam pengumpulan data digunakan teknik tes dan nontes. Berdasarkan hasil penelitian terhadap 30 siswa diketahui keterampilan rata – rata siswa dalam menulis teks eksplanasi adalah 76,63 dari skor total 100 dengan nilai konversi 3,04 atau predikat B. Hasil penelitian tentang keterampilan menulis teks eksplanasi siswa berdasarkan aspek isi, organisasi, kosakata, penggunaan bahasa, dan mekanik adalah Baik. Namun, siswa masih kesulitan untuk mengembangkan kalimat dari ide yang sudah ada. Selain itu, siswa masih sering melakukan kesalahan dalam penulisan isi dan struktur teks. Penulis ingin menyarankan guru untuk menggunakan metode inquiry learning dengan setting mind mapping technique dalam mengajar menulis teks eksplanasi, karena metode ini dapat mempromosikan ekspresi yang menyenangkan dalam menulis, sehingga mendapat partisipasi yang lebih besar di antara siswa.Kata kunci: Teks Eksplanasi , Metode Inquiry learning, Mind Mapping Technique.